Acentua Fácil: A system to support Brazilian Portuguese Accentuation - Staniecki, Gabriella Selbach; Astrogildo, Larissa de Freitas; Primo, Tiago Thompsen (Anais do Workshop on Advanced Virtual Environments and Education (WAVE); 2020: Anais do III Workshop on Advanced Virtual Environments and Education, 2021)
The main objective of Acentua Facil is to assist students in the writing ´ process and teachers in the learning process. This article presents a system to aid the accentuation process for Brazilian Portuguese. The input of the system is texts. These texts are analyzed through the use of grammatical rules and artificial intelligence(IA) techniques such as tokenization. For each word in the text, we show the graphic accentuation errors, together with explanations of how it should be a correct word.From the results we were able to use some validation metrics, such as histograms and confusion matrix, both of which are used when working with AI.